Pemberdayaan UMKM Desa Wisata melalui Digital Marketing, Artificial Intelligence, `Literasi Hukum Bisnis, dan Green Business untuk Meningkatkan Daya Saing Usaha di Kabupaten Pesawaran, Provinsi Lampung - Rinaldi Bursan; Dina Safitri; Aida Sari; Driya Wiryawan; Prakarsa Panjinegara; Faila Shofa; Ramadhani Sanjaya; Doni Sagitarian Warganegara; Dita Febrianto (Lembaga Pengembangan Kinerja Dosen, 2026)
In tourist village regions, micro, small, and medium-sized enterprises (MSMEs) play an important role in strengthening the local economy and supporting sustainable tourism. However, MSME players in Pesawaran Regency, Lampung Province, still face challenges in utilizing digital technology, artificial intelligence (AI), and green business practices. This community service program aims to improve MSME capabilities through training and mentoring in digital marketing, AI, and green business implementation. Thirty MSME players from tourist villages participated through coaching, experiential learning, asset-based community development (ABCD), and participatory rural appraisal (PRA). Evaluation was conducted using pre-tests and post-tests. The results showed increased participant knowledge from 29.5% to 88.7%, AI utilization skills from 13.3% to 86.7%, and Google Business Profile ownership from 16.7% to 83.3%. Participants also adopted environmentally friendly packaging, developed brand identities, expanded digital promotion networks, and implemented digital marketing strategies. Participant satisfaction reached an average score of 4.79 out of 5. These results demonstrate that integrating digital marketing, AI, and green business practices can improve MSME capabilities, competitiveness, and sustainability in tourist villages